Clinical, Neuroimaging, and Electroencephalographic Spectrum of Patients with Isolated Nocturnal Seizures: An Experience at a Tertiary Care Center - Shivde, Sonia; Badachi, Sagar; Nadig, Raghunandan; D'Souza, Delon; Kapparath, Sreerag; T., Elizabeth V.; Mathew, Thomas; Deepalam, Saikanth; G., Sharath Kumar G.; Sarma, G.R.K. (International Journal of Epilepsy, 2025)
This article studies clinical, neuroimaging, and electroencephalographic profile of patients with isolated nocturnal seizures (NS).We prospectively analyzed a cohort of 70 patients with pure sleep-related seizures over the period of 5 years. Patients having seizures during wake state were excluded. Patients were divided into two groups based on time of seizure occurrence—that is, from time of onset of sleep till 3 a.m. and from 3 to 6 a.m. Clinical details of seizures, routine awake-sleep electroencephalogram (EEG), video EEG (VEEG), and neuroimaging findings were analyzed.The mean age at the onset of seizure was 26 years. Male-to-female ratio was 4:3. Two-thirds of patients (68.5%) had seizure episodes within initial hours of sleep, that is, till 3 a.m. The most common semiology observed was Generalised Tonic Clonic Seizuree (GTCs) (71.42%). Majority (81.4%) of the patients had normal routine EEG (wake and sleep record), while 40% of cases had abnormal VEEG findings. The most common abnormality detected was calcified granuloma. The most commonly involved region was the frontal lobe, and left side lesions dominated over the right. Sixty-five percent of patients maintained good seizure control on monotherapy.NS can distort the sleep architecture and impair the quality of life. Prolonged night time VEEG and neuroimaging can be valuable for better characterization of seizure semiology. Left hemispheric and frontal lobe lesions may have a role in sleep-associated epilepsies. Despite being difficult to diagnose due to their untimely occurrence, NS once detected and managed can have a good treatment outcome.
Keywords: epilepsy; sleep; EEG